A flux estimation method for three‐phase dual‐active‐bridge DC/DC converters. Issue 6 (12th March 2021) - Nguyen, Duy‐Dinh; Goto, Takuya; Yukita, Kazuto; Katou, Akinori; Yoshida, Shinji
Abstract: This study proposes an estimation method of flux density in high‐frequency transformers of three‐phase dual‐active‐bridge transformers. The steady‐state analysis shows that the flux in the converter is different in Buck and Boost modes and depending on load and voltage gain condition. From that, a closed‐form formula is proposed to estimate the flux swing in the core. Unlike the conventional estimation technique, the proposed one represents the flux as a function of input and output voltages and the phase shift value. Finite element analysis confirms that the proposed formula can predict the flux with less than 4% error. The proposed formula can also help to improve the prediction of temperature profile of the transformers with a high accuracy of less than 1 degree Celsius in the mid‐ to high‐power range as validated in experiments. The proposed flux estimation method can be used in designing the converter or in predicting the converter behaviour under critical conditions such as load changing or starting, and so forth, to help protect the transformers from saturation or DC bias.